2005
DOI: 10.1139/z05-022
|View full text |Cite
|
Sign up to set email alerts
|

Do carotenoids and spleen size vary with helminth load in greylag geese?

Abstract: It has been suggested that carotenoid-derived coloration serves as an indicator of parasite levels and (or) the general health of birds. We investigated relationships among spleen size (sometimes considered an indicator of the cellular immune response capacity of birds), carotenoid level, helminth load, and leg and bill coloration of greylag geese, Anser anser (L., 1758), from Doñana National Park (southwest Spain). Nematode abundance was positively related to spleen size and negatively to body condition, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
(45 reference statements)
1
12
0
2
Order By: Relevance
“…; Righi & Gauthier ; Figuerola et al . ; Mazur, Pronin & Tolochko ) as compared to mammals (Bordes & Morand ,b and references therein). These studies suggest that tapeworm infections are frequent in natural bird populations and are often associated with significant inflammatory and cellular immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Righi & Gauthier ; Figuerola et al . ; Mazur, Pronin & Tolochko ) as compared to mammals (Bordes & Morand ,b and references therein). These studies suggest that tapeworm infections are frequent in natural bird populations and are often associated with significant inflammatory and cellular immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only few Table 5. Summary table of the relationships found between measured immunological indices and (a) individual parasites (+: significantly positive correlation, À: significantly negative correlation or 0: not significant; see Table 3 for more details) or with (b) multiple parasites (parasites main effects and in interaction, see studies examined immune indices in relation to multiple parasite species (Figuerola et al 2005;Valera, Herbert & Kristin 2006;Go€ uy de Bellocq et al 2007;Roulin et al 2007). The differential influence of two intestinal parasites on the immune response to PHA supports the results found in white-toothed shrews, where immune response to PHA was negatively related to cestode intensity and positively related to nematode intensity (Go€ uy de Bellocq et al 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, unlike in feathers, the expression of carotenoids in integuments is dynamic and may respond to changes in individual condition (Faivre et al 2003a;Pérez-Rodríguez and Viñuela 2008). Predictions of PMSS have been tested in carotenoid-coloured integuments (Figuerola et al 2005;Martínez-Padilla et al 2007;Baeta et al 2008;Mougeot et al 2010), and the colouration of ornaments has been found to be related to indicators of health (McGraw and Ardia 2003;Bertrand et al 2006;Mougeot 2007;Mougeot et al 2007Mougeot et al , 2009 and reproductive ability (Massaro et al 2003;Peters et al 2004;McGraw et al 2005;Hill and McGraw 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Cornet, Biard & Moret (2007) found a positive relationship between carotenoid concentration in haemolyymph and immune parameters (those evolved in the prophenoloxidase cascade) in the crustacean Gammarus pulex, suggesting that carotenoids can help to reduce the costs of immunity by limiting self-harming. A positive relationship between carotenoid concentration and the abundance of cestodes (but not of nematodes) was also observed in greylag geese Anser anser (Figuerola et al, 2005), suggesting there may be a similar host response to cestode infection across a broad taxonomic range. The proportion of infected shrimps with a red colour was higher for A. salina than for A.…”
Section: Castration and Colour Effects In Native And Alien Hostsmentioning
confidence: 74%